Effectiveness of ozone therapy in maxillary osteonecrotic lesions – Literature review (Research, Society and Development, 2021)
The use of ozone in dentistry has been indicated due to its properties. These have made it an important adjunct in the management of various dental situations. The mechanism of action makes ozone therapy a technique with several attractions for dental specialties. Stomatology has benefited from studies on the subject, especially the management of osteonecrotic lesions of the jaws. Through a literature review, the objective of this work is to summarize the different possibilities of using ozone within dental specialties, highlighting its applicability in the prevention and treatment of osteonecrosis of the jaws. It was observed that ozone therapy proved to be a versatile and effective tool, behaving as an immune system helper, favoring the repair of dental diseases with a chronic and / or acute character. Ozone has also been shown to be a potent reducer of complications when it comes to patients at risk of developing osteonecrosis, in addition to contributing to the healing of already established injuries.